2021
DOI: 10.3389/fnins.2021.682208
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Function in Anorexia Nervosa: A Systematic Review

Abstract: Background: Autonomic nervous system (ANS) dysfunction has been suggested to contribute to the high prevalence of cardiovascular complications in individuals with anorexia nervosa (AN), yet has not been thoroughly investigated. The current review aimed to synthesize the evidence of basal ANS function in individuals with a current diagnosis of AN and those with a previous diagnosis who had achieved weight restoration, as compared to controls.Methods: A systematic review of nine databases was conducted and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 121 publications
0
7
0
Order By: Relevance
“…They also often show increased levels of alexithymia, that is, difficulties in identifying and describing emotional states [52, 53], and decreased levels of interoception, that is, awareness of bodily signals [54]. Increased parasympathetic activity in the acute state of the disorder might also reduce the subjective experience of arousal [55, 56]. It could therefore be argued that we found conflict strength to be less relevant for self-control success in AN patients because, similarly to emotional states, self-control conflicts are experienced less intensely.…”
Section: Discussionmentioning
confidence: 99%
“…They also often show increased levels of alexithymia, that is, difficulties in identifying and describing emotional states [52, 53], and decreased levels of interoception, that is, awareness of bodily signals [54]. Increased parasympathetic activity in the acute state of the disorder might also reduce the subjective experience of arousal [55, 56]. It could therefore be argued that we found conflict strength to be less relevant for self-control success in AN patients because, similarly to emotional states, self-control conflicts are experienced less intensely.…”
Section: Discussionmentioning
confidence: 99%
“…Mazurak et al (2011a;20 studies; N = 739) found mixed results regarding HRV patterns in AN, and Peyser and colleagues (2021) found elevated HRV in AN compared to healthy individuals (20 studies). Jenkins et al (2021) reported increased parasympathetic and decreased sympathetic activity in AN as measured by HRV, EDA, and other PP (46 studies; N = 934). Three reviews found inconsistent results (HRV in BN [Peschel et al, 2016;17 studies;N = 1441], PP in acute stress in Binge eating disorder (BED) [Naish et al, 2019;14 studies], and HRV in BED [Christensen et al, 2023;6 studies;N = 153]).…”
Section: Prior Reviewsmentioning
confidence: 99%
“…Jenkins et al. (2021) reported increased parasympathetic and decreased sympathetic activity in AN as measured by HRV, EDA, and other PP (46 studies; N = 934). Three reviews found inconsistent results (HRV in BN [Peschel et al., 2016; 17 studies; N = 1441], PP in acute stress in Binge eating disorder (BED) [Naish et al., 2019; 14 studies], and HRV in BED [Christensen et al., 2023; 6 studies; N = 153]).…”
Section: Introductionmentioning
confidence: 99%
“…Interoception deficits (i.e., the difficulty to accurately identify internal physiological signals like hunger or satiety), have been identified as a key symptom in network analysis of AN psychopathology [ 23 ]. Therefore, there is a venue for further research on the autonomic nervous system in AN [ 24 ] using sensing technology.…”
Section: Introductionmentioning
confidence: 99%